2017
DOI: 10.4103/ijnmr.ijnmr_66_16
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, burnout, demographic variables and their relationships in oncology nurses

Abstract: Introduction:Development of nurse–patient empathic communication in the oncology ward is of great importance for the patients to relieve their psychological stress, however, nursing care of cancer patients is accompanied with high stress and burnout. The present study aimed to define the level of empathy and its association with burnout and some demographic characteristics of oncology nurses.Materials and Methods:This descriptive/correlation study was conducted in a professional cancer treatment center in Isfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
25
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 34 publications
3
25
0
4
Order By: Relevance
“…Similar data were found in a study with oncologist nurses. 5 It is believed that some authors associate the longer time in the oncology area, as in the case of this study, to a higher tendency to Burnout, since the professional would enter a period of sensitization becoming more vulnerable. This awareness is due to the fact that, after a certain period of professional practice, there has been a transition from the initial idealistic expectations of the profession to the daily practice, visualizing that the personal, professional and economic rewards are not the same as those expected.…”
Section: Datamentioning
confidence: 63%
See 2 more Smart Citations
“…Similar data were found in a study with oncologist nurses. 5 It is believed that some authors associate the longer time in the oncology area, as in the case of this study, to a higher tendency to Burnout, since the professional would enter a period of sensitization becoming more vulnerable. This awareness is due to the fact that, after a certain period of professional practice, there has been a transition from the initial idealistic expectations of the profession to the daily practice, visualizing that the personal, professional and economic rewards are not the same as those expected.…”
Section: Datamentioning
confidence: 63%
“…It is necessary to see the student in a holistic way, part of diversified life trajectories, and the nursing areas most lacking in qualified professionals such as oncology, since the real choice for acting in oncology can happen after the professional experience in the area, such as was investigated in this study and in agreement with the literature. 5,8 It is believed that the training of nurses, in the XXI century, must envisage a continuous acquisition of knowledge in order to act effectively in the health team and in the greater interest, which is the patient he attended.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…수평적 폭력을 악화시키는 요인 중 하나로 역기능적 의사 소통이 보고되었는데 (Rosenstein et al, 2008), 상호적인 의사소통이 아닌 일방적인 의사소통이나 표현되지 않는 갈 등과 침묵 등의 역기능적 의사소통은 상대방과의 갈등을 초 래하고 분노와 수평적 폭력을 악화시킨다 (Duxbury et al, 2005;Choeng SH et al, 2016). 반면 간호사의 효과적인 의사소통은 간호사 스스로의 소진을 낮출 뿐만 아니라, 간호 사와 환자의 관계에서 환자가 느낄 수 있는 스트레스를 완화 하고 건강한 치료적 관계를 조성하는데 중요한 요인이다 (Fariba et al, 2017;Kim HJ, 2018). 간호사들이 경험한 수평적 폭력에 대한 질적 연구에서는 자기 표현, 쌍방향적 의사소통이 수평적 폭력을 완화하고 관계 형성에 도움을 주 는 것으로 나타났다 (Kang JY et al, 2016).…”
unclassified
“…21 Another study carried out in the Isfahan Province, in Iran, with oncology nurses, highlighted the need for intervention programs to relieve stress and prevent these professionals from being fatigued, as they play an important role in the care of cancer patients. 28 Psychological and emotional disturbances are expected, due to the highly demanding technical care provided, which can lead to a commotion to be experienced by these workers in their routine. 29 A study conducted in the UK with oncology nurses and community nurses assessed their self-reported skills and demonstrated that community nurses were less confident in recognizing the late symptoms of the disease, and identified a greater need for training, as their role is continuous in monitoring patients with cancer.…”
mentioning
confidence: 99%